The messages presented in online electronic cigarette promotions and discussions: a scoping review protocol - McCausland, Kahlia; Maycock, B.; Jancey, J. (BM J Group, 2017)
Introduction: Electronic cigarettes have become increasingly popular over the last 10 years. These devices represent a new paradigm for tobacco control offering smokers an opportunity to inhale nicotine without inhaling tobacco smoke. To date there are no definite conclusions regarding the safety and long-term health effects of electronic cigarettes; however, there is evidence that they are being marketed online as a healthier alternative to traditional cigarettes. This scoping review aims to identify and describe the breadth of messages (eg, health, smoking-cessation and price related claims) presented in online electronic cigarette promotions and discussions. Methods and analysis: A scoping review will be undertaken adhering to the methodology outlined in The Joanna Briggs Institute Manual for Scoping Reviews. Six key electronic databases will be searched to identify eligible studies. Studies must be published in English between 2007 and 2017, examine and/or analyse content captured from online electronic cigarette promotions or discussions and report results for electronic cigarettes separately to other forms of tobacco delivery. Studies will be screened initially by title and abstract, followed by full-text review. Results of the search strategy will be reported in a PRISMA flow diagram and presented in tabular form with accompanying narrative summary. Ethics and dissemination: The methodology consists of reviewing and collecting data from publicly available studies, and therefore does not require ethics approval. Results will be published in a peer reviewed journal and be presented at national/international conferences. Additionally, findings will be disseminated via social media and online platforms. Advocacy will be key to informing policy makers of regulatory and health issues that need to be addressed. Registration details: The review was registered prospectively with The Joanna Briggs Institute Systematic Reviews database.